2023
DOI: 10.2147/dmso.s404127
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Comorbid Obesity in Chinese Patients with Bipolar Disorder

Abstract: Purpose Bipolar disorder (BD) predisposes patients to comorbid obesity and increases the risk of metabolic syndrome and cardiovascular disease. In this study, we investigated the prevalence of comorbid obesity and its risk factors in patients with BD in China. Patients and Methods We conducted a cross-sectional retrospective survey of 642 patients with BD. Demographic data were collected, physical examinations were performed, and biochemical indexes, including fasting b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Existing studies have shown sex differences in the duration and type of attacks in male and female patients with BD, 26 but little is known about the presence of comorbid NAFLD, making it particularly important to investigate risk factors for comorbid NAFLD in different sexes. Our previous study find significantly higher rates of comorbid obesity in patients with BD and higher plasma levels of ALT, blood glucose, uric acid and TG in obese patients; 7 building on this finding, we take it a step further to examine sex differences in comorbid NAFLD in patients with BD, targeting sex-specific risk factors.…”
Section: Discussionmentioning
confidence: 88%
“…Existing studies have shown sex differences in the duration and type of attacks in male and female patients with BD, 26 but little is known about the presence of comorbid NAFLD, making it particularly important to investigate risk factors for comorbid NAFLD in different sexes. Our previous study find significantly higher rates of comorbid obesity in patients with BD and higher plasma levels of ALT, blood glucose, uric acid and TG in obese patients; 7 building on this finding, we take it a step further to examine sex differences in comorbid NAFLD in patients with BD, targeting sex-specific risk factors.…”
Section: Discussionmentioning
confidence: 88%
“… 58 , 59 The most explicit thing was the use of antipsychotics, especially atypical antipsychotics. 60 The metabolic side effects of antipsychotic drugs in the clinical population are now well established. 61 Norepinephrine, epinephrine and catecholamine are hormones that are very important in the regulation of many metabolic processes.…”
Section: Discussionmentioning
confidence: 99%
“…As is widely known, mental disorders, including BD, can influence a range of metabolic changes such as blood lipids. In our extensive literature review, we found that most studies have focused on the impact of BD on MS (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%